2017
DOI: 10.21769/bioprotoc.2424
|View full text |Cite
|
Sign up to set email alerts
|

Primary Culture System for Germ Cells from Caenorhabditis elegans Tumorous Germline Mutants

Abstract: The Caenorhabditis elegans germ line is an important model system for the study of germ stem cells. Wild-type C. elegans germ cells are syncytial and therefore cannot be isolated in in vitro cultures. In contrast, the germ cells from tumorous mutants can be fully cellularized and isolated intact from the mutant animals. Here we describe a detailed protocol for the isolation of germ cells from tumorous mutants that allows the germ cells to be maintained for extended periods in an in vitro primary culture. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The in vitro culture of isolated glp-1(gf); cki-2; daf-16 germ cells in CeM1 medium with stimulatory bacterial extract and folates was as described (Vagasi et al, 2017). Δ 7 -DA or Δ 4 -DA (both from Cayman Chemical Co.) or DMSO or ethanol carrier controls, respectively, were included in the CeM1 medium.…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro culture of isolated glp-1(gf); cki-2; daf-16 germ cells in CeM1 medium with stimulatory bacterial extract and folates was as described (Vagasi et al, 2017). Δ 7 -DA or Δ 4 -DA (both from Cayman Chemical Co.) or DMSO or ethanol carrier controls, respectively, were included in the CeM1 medium.…”
Section: Methodsmentioning
confidence: 99%
“…Lysing the worms is the critical step during this method since it is of crucial importance that DNA damages are not caused by the lysing process itself. We found that gentle sonification (Ultrasonic Processor, UP 100H, 2 × 20 s, in 1 mL liquid) works better for that purpose than using chemical dissipation of the cuticle (e. g. protein kinase K, pronase E, papain, Triton X-100), breaking of the cuticle with high pressure (French pressure cell press, as used for yeast cell lysis (Moore et al 2016)) or slicing worms using syringes as described for germ cell isolation (Vagasi et al 2017). Except for the gentle sonification, the other methods resulted in additional DNA damage as we detected only very low amounts of dsDNA (data not shown).…”
Section: Methods Developmentmentioning
confidence: 99%